Neutron Yield From Gamma Ray Incineration of Radioactive Fission Products - Al-Bayati, Abdul-Hussain A. (Iraqi Journal of Physics, 2010)
The neutron flux in this paper, which is generated as a result of γ incineration of the radioactive fisssion products isotopes has been evaluated .It is obvious from this paper that the neutron flux value depends on the number of incineration nuclei and the nuclear cross-section of the incinerated isotopes, and the neutron flux is directly dependent on γ-ray flux. The neutron flux increases from 1010to 1017n/s.gm as the irradiation flux increases from 1016to 1020 γ/cm2.s. It is concluded that the γ-incineration technique can be used to produce a switchable neutron source of high flux.